THE R LANGUAGE AS A TOOL FOR CORPORATE DECISION MAKING - Okada Spinelli, Gabriel; Malagolli, Guilherme (Revista Interface Tecnológica, 2024)
Data analytics, applied to the corporate environment, enables the collection, processing and interpretation of data to find patterns, anomalies, trends and correlations in large data sets to predict results. Through a variety of techniques, you can use this information to increase income, cut costs, improve customer relationships and reduce risks. Therefore, the great advantage of this process is that it facilitates decision-making, making decisions more precise by identifying trends and risks more clearly. In this context, the objective of this article is to investigate how the R programming language can be more effective in data analysis than previous languages ​​and how it contributes to more accurate decision-making by businesspeople. It was concluded that the R language can improve decision-making in various segments of the company, such as recruitment, retention, production decisions, performance evaluation and market trends.
Keywords: Data analysis; Competitiveness; Programming language; Decision making